BEYOND THE GAME: ANALYZING THE USEFULNESS OF GAMES TO PROMOTE LIFE SKILLS DEVELOPMENT - André, Mauro Henrique; Mandigo, James Lloyd (Pensar a Prática, 2013)
The current paper provides a reflection about games’ ‘power’ to promote both ‘good’ and ‘bad’ learning. The study is organized in three sections. First, the complexity of games’ nature is briefly introduced within diverse perspectives in order to provide an understanding why games are highly empowered. Second, an analysis of historical events and academic references show how games have been used to promote both good and bad events. Finally, two life experiences are presented in order to illustrate how games can provide opposite outcomes regardless of cultural differences. Thus, within a provocative reflexive, physical educators are encouraged to think what can be taught on their daily lesson that is “beyond” the learning of the game itself.